Menilik Reaksi Pasar Terhadap Pengumuman Rilis Fatwa MUI No. 83 Tahun 2023 - Gunibala, Zakir; Renuat, Andini; Dzikriah, Sukmawati Indah (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2024)
Abstract: Examining the Market Reaction to the Announcement of the Release of MUI Fatwa No. 83 Year 2023Purpose: Revealing the market reaction that has an impact on the stimulus in the form of MUI's fatwa on the appeal not to use Israeli-affiliated products released in November 2023.Method: Quantitative method of case study approach. Using statistical analysis of 14 samples of companies listed on the IDX. Data obtained from the IDX and Yahoo Finance pages.Results: Shows that there is no AR and no significant difference during the event period studied. TVA shows significant statistical analysis results.Novelty: The current issue raised, which is related to the announcement of MUI fatwa no. 83 of 2023 concerning the appeal not to use products affiliated with Israel.Contribution: Expand the literature of market reaction studies with the latest relevant issues.nouncement of MUI fatwa no. 83 of 2023 concerning the appeal not to use products affiliated with Israel. Abstrak: Menilik Reaksi Pasar Terhadap Pengumuman Rilis Fatwa MUI No. 83 Tahun 2023Tujuan: Mengungkap reaksi pasar yang berdampak pada stimulus berupa penerbitan fatwa oleh MUI tentang imbauan menghindari produk terafiliasi Israel pada November 2023.Metode: Metode kuantitatif pendekatan studi kasus menggunakan analisis statistik terhadap 14 sampel perusahaan yang diperoleh dari laman BEI dan Yahoo Finance.Hasil: Mengungkapkan tidak adanya AR serta tidak ada signifikansi perbedaan selama Jendela Peristiwa yang diobservasi. TVA menunjukkan hasil analisis statistik yang signifikan.Kebaruan: terletak pada isu yang diangkat saat ini, yaitu terkait dengan pengumuman fatwa MUI no. 83 tahun 2023 tentang himbauan untuk tidak menggunakan produk yang berafiliasi dengan Israel.Kontribusi: Memperluas literatur kajian reaksi pasar dengan isu terbaru yang relevan.